2016
DOI: 10.5395/rde.2016.41.3.189
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of a newly produced resin-based endodontic sealer

Abstract: ObjectivesA variety of root canal sealers were recently launched to the market. This study evaluated physicochemical properties, biocompatibility, and sealing ability of a newly launched resin-based sealer (Dia-Proseal, Diadent) compared to the existing root canal sealers (AHplus, Dentsply DeTrey and ADseal, Metabiomed).Materials and MethodsThe physicochemical properties of the tested sealers including pH, solubility, dimensional change, and radiopacity were evaluated. Biocompatibility was measured using the 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 22 publications
2
35
0
1
Order By: Relevance
“…AH-Plus (Dentsply DeTrey, Konstanz, Germany) is the most popular hydrophobic epoxy resin-based sealer that has been used as the gold standard material [ 3 ]. AD Seal (Meta Biomed, Cheongju, Korea) and Radic-Sealer (KM, Seoul, Korea) are the epoxy resin-based sealers with few reports in literature [ 15 , 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…AH-Plus (Dentsply DeTrey, Konstanz, Germany) is the most popular hydrophobic epoxy resin-based sealer that has been used as the gold standard material [ 3 ]. AD Seal (Meta Biomed, Cheongju, Korea) and Radic-Sealer (KM, Seoul, Korea) are the epoxy resin-based sealers with few reports in literature [ 15 , 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…The increase in the mass of Adseal samples is also supported by the results of the present study. Other researchers also significantly show that Adseal is increasing in weight and volume and has the lowest solubility among the substances they studied [2].…”
Section: Figure 9 Flow Rate Of the Examined Sealer Samplesmentioning
confidence: 83%
“…The ideal root filling must be insoluble, biocompatible, and must remain dimensionally stable after being inserted into the canal. By dimensional change of the sealers we mean shrinkage or expansion of the material after setting, expressed as a percentage [2].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the radiopacity of the AH Plus is approximately 7.8 mm Al when measured with the scanner, PSP and digital sensor, 7 9.8 mm Al, with the scanner, 4 10.41 mm Al, with the CCD digital sensor 26 and 14 mm Al, with the photodensitometer. 27 The divergent information on AH Plus radiopacity 4,7,27 could be attributed to the use of different devices used and methodologies applied.…”
Section: Discussionmentioning
confidence: 99%